Antenas Leaky-Waves Acústicas Moduladas. - Campo-Valera, María; Fernández-Garrido, Alejandro; Gómez-Tornero, José Luis (My University, 2022)
This paper shows for the first time the ability of Acoustic Leaky-Wave antennas (ALWAs) to modulate the phase and the leakage rate of the constituent leaky mode. This feature is crucial to synthesize shaped acoustic beams, which can be scanned in the angular space by just sweeping the operational frequency. We provide examples of directive acoustic beams with reduced sidelobes level, sectorized broad beam patterns, and near-field focused acoustic spots. These types of acoustic beams can be used to improve the performance of novel and low-cost SONAR designs, based on ALWAs.
Keywords: Antenas; Antenas leaky-waves; Propagación acústica; Ángulo de escaneo; Directividad